Upgrading pyrolysis bio-oil to biofuel over bifunctional Co-Zn/HZSM-5 catalyst in supercritical methanol. (1st September 2017) - Cheng, Shouyun; Wei, Lin; Julson, James; Muthukumarappan, Kasiviswanathan; Kharel, Parashu Ram
Highlights: Integration of Co-Zn/HZSM-5 and supercritical methanol was used for bio-oil hydrodeoxygenation. Co-Zn/HZSM-5 exhibited higher effectiveness than Co/HZSM-5 or Zn/HZSM-5. 15%Co5%Zn/HZSM-5 produced biofuel with the highest hydrocarbons content at 35.33%. Loading of Co and/or Zn did not change crystalline structure of HZSM-5. Hydrogenation and esterification are main reactions in bio-oil hydrodeoxygenation. Abstract: The role of catalyst is essential in processes of upgrading biomass pyrolysis bio-oil into hydrocarbon biofuel. While the majority of heterogeneous catalytic processes are conducted in the presence of gas (nearly ideal) or liquid phase, a growing number of processes are utilizing supercritical fluids (SCFs) as reaction media. Although hydrodeoxygenation (HDO) is proven a promising process for pyrolysis bio-oil upgrading to hydrocarbon biofuel, catalyst efficiency remains a challenge. Integrating heterogeneous catalysts with SCFs in a bio-oil HDO process was investigated in this study. Bifunctional Co-Zn/HZSM-5 catalysts were firstly used to upgrade bio-oil to biofuel in supercritical methanol. The loading of Co and Zn did not change HZSM-5 crystalline structure. Physicochemical properties of biofuel produced by Co and/or Zn loaded HZSM-5 catalysts such as water content, total acid number, viscosity and higher heating value improved. Bimetallic Co-Zn/HZSM-5 catalysts showed enhanced reactions of decarboxylation and decarbonylation that resulted in higher yields of CO and CO2 . Bimetallic Co-Zn/HZSM-5 catalysts were more effective for bio-oil HDO than monometallic Co/HZSM-5 or Zn/HZSM-5 catalyst, which was attributed to the synergistic effect of Co and Zn on HZSM-5 support. Bimetallic Co-Zn/HZSM-5 catalysts increased biofuel yields and hydrocarbons contents in biofuels in comparison with monometallic Co/HZSM-5 and Zn/HZSM-5 catalysts. 5%Co15%Zn/HZSM-5 catalyst generated the highest biofuel yield at 22.13 wt.%, and 15%Co5%Zn/HZSM-5 catalyst produced biofuel with the highest hydrocarbons content at 35.33%. Hydrogenation and esterification are two dominant reactions in bio-oil HDO over Co-Zn/HZSM-5 catalysts in supercritical methanol. The energy efficiency of biofuel product was 30.99–58.80% for Co-Zn/HZSM-5 catalysts. Co-Zn/HZSM-5 is a promising catalyst to produce biofuel with high quality in bio-oil HDO.